2003
DOI: 10.3808/jei.200300016
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Urban Land-Use and Land-Cover Changes in Mississauga Using Landsat TM Images

Abstract: ABSTRACT. The City of Mississauga in Ontario has been experiencing a fast urban growth in the past two decades which has caused rapid loss of the valuable farm and open space land. Land-use and land-cover maps of the City were produced from Landsat TM images for 1985 and 1999, spanning a period of 14 years. Dramatic changes in land use and land cover have occurred, with loss of forest, cropland and water body to urban use. In particular, low-density urban use, which includes largely residential use, has increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Landsat images have been extensively utilized for UHI study (Buyantuyev, Wu, and Gries 2007;Kato and Yamaguchi 2005;Li and Zhao 2003;Lu and Weng 2005;Sobrino, Jimenez-Munoz, and Paolini 2004;Srivastava, Majumdar, and Bhattacharya 2009). Landsat 5 provides TM images that have six bands in the visible and near infrared regions with 30 m spatial resolution, and one thermal infrared band with 120 m spatial resolution.…”
Section: Study Area and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Landsat images have been extensively utilized for UHI study (Buyantuyev, Wu, and Gries 2007;Kato and Yamaguchi 2005;Li and Zhao 2003;Lu and Weng 2005;Sobrino, Jimenez-Munoz, and Paolini 2004;Srivastava, Majumdar, and Bhattacharya 2009). Landsat 5 provides TM images that have six bands in the visible and near infrared regions with 30 m spatial resolution, and one thermal infrared band with 120 m spatial resolution.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Dewan and Yamaguchi (2009) found that substantial growth of built-up areas in Greater Dhaka resulted in a significant decrease in the area of water bodies, cultivated land, vegetation, and wetlands. In addition, rapid urban expansion induced a wide range of environmental impacts, including habitat quality (Bayarsaikhan et al 2009;Dewan and Yamaguchi 2009;Li and Zhao 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For a 17-year land cover change analysis, the City of Mississauga is divided into four different sections according to the administrative map and using existing roads as natural boundaries. The four sections are southeast region, middle part, international airport area and northwest section (Li and Zhao, 2004). In each section, evaluating points are randomly generated using the same method as in accuracy assessment procedure.…”
Section: V-i-s Pattern Recognitionmentioning
confidence: 99%
“…Examining LULC change in the last few decades has become an increasing concern because of biodiversity decreasing, habitat changing, and altering the regional and global climate patterns and composition (J. Li & Zhao, 2003;Lilly Rose, 2009;Mishra & Rai, 2016). It can be challenging, complicated, and likely to yield contradictory results to detect and tests changes in LULC through direct field visits (Meyer & Turner, 1992;M.…”
Section: Introductionmentioning
confidence: 99%